2017
DOI: 10.3390/genes8100245
|View full text |Cite
|
Sign up to set email alerts
|

BARHL1 Is Downregulated in Alzheimer’s Disease and May Regulate Cognitive Functions through ESR1 and Multiple Pathways

Abstract: The Transcription factor BarH like homeobox 1 (BARHL1) is overexpressed in medulloblastoma and plays a role in neurogenesis. However, much about the BARHL1 regulatory networks and their functions in neurodegenerative and neoplastic disorders is not yet known. In this study, using a tissue microarray (TMA), we report for the first time that BARHL1 is downregulated in hormone-negative breast cancers and Alzheimer’s disease (AD). Furthermore, using an integrative bioinformatics approach and mining knockout mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(16 citation statements)
references
References 105 publications
0
16
0
Order By: Relevance
“…BARHL1 was detected overexpressing in medulloblastoma and played an important role in neurogenesis. BARHL1 was downregulated in Alzheimer's Disease and other psychiatric disorders [26]. The changing binding of these transcription factors by mutation of rs6678136 might induced psychiatric disorders.…”
Section: Discussionmentioning
confidence: 97%
“…BARHL1 was detected overexpressing in medulloblastoma and played an important role in neurogenesis. BARHL1 was downregulated in Alzheimer's Disease and other psychiatric disorders [26]. The changing binding of these transcription factors by mutation of rs6678136 might induced psychiatric disorders.…”
Section: Discussionmentioning
confidence: 97%
“…Barhl genes have a crucial role in the control of neuronal subtype acquisition and maintenance during development and in the adult 1,2,5,6,8,14,54 . Loss of Barhl2 protein in the postnatal mammalian retina causes programmed cell death of more than 50% of RGCs 13 .…”
Section: Discussionmentioning
confidence: 99%
“…BarH-like homeodomain (BARHL) transcription factors play crucial roles in the control of neural cell fate specification, migration, subtype identity acquisition and survival during development of the retina and the brain [1][2][3][4][5][6][7] . Studies have also implicated Barhl in neurodegenerative and neoplastic disorders 8,9 . In Xenopus and mouse, barhl2 appears to be the only family member expressed in the retina 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous research has suggested that the transplantation of BMSCs overexpressing NT-3 could promote recovery of locomotor function and nerve regeneration in a rat model of spinal cord injury (Wang et al, 2014 ). Recent study showed that NT-3 probably binds to the Brain Derived Neurotrophic Factor (BDNF) and jointly regulate neurogenesis and neural survival (Barh et al, 2017 ). Based on the above research, we speculated that the transplantation of BMSCs modified with the gene for NT-3 could have an impact on nerve regeneration and recovery of cognitive function that might be relevant to the treatment of AD.…”
Section: Introductionmentioning
confidence: 99%